Cluster Conversation: Dr. Pingdewindé Tiendrebeogo and Ute Fendler (2024)
Dr. Pingdewindé Issiaka TIENDRÉBÉOGO is a lecturer and researcher in theatre studies at the Joseph KI-ZERBO University in Ouagadougou, Burkina Faso. In May 2024 he was guest of the Africa Multiple Cluster of Excellence for an event with Umar Timol from Mauritius. In this interview he talks with Prof. Dr. Ute Fendler about theatre in Burkina Faso and his own work.